2019
DOI: 10.15447/sfews.2019v17iss3art2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drought and the Emergency Drought Barrier on the Ecosystem of the California Delta

Abstract: In 2015, the fourth year of the recent drought, the California Department of Water Resources installed a rock barrier across False River west of Franks Tract to limit salt intrusion into the Delta at minimal cost in freshwater. This Barrier blocked flow in False River, greatly reducing landward salt transport by decreasing tidal dispersion in Franks Tract. We investigated some ecological consequences of the Barrier, examining its effects on water circulation and exchange, on distributions of submerged aquatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Water year 2014 was classified as critically dry in the Sacramento Valley [33]. For this reason, salinity conditions were fairly static during the simulation period with a slow increasing trend ( Figure 5).…”
Section: Hydrodynamic Model Calibrationmentioning
confidence: 99%
“…Water year 2014 was classified as critically dry in the Sacramento Valley [33]. For this reason, salinity conditions were fairly static during the simulation period with a slow increasing trend ( Figure 5).…”
Section: Hydrodynamic Model Calibrationmentioning
confidence: 99%
“…As previously noted, the historic drought of 2012-2106 resulted in major challenges in preventing salinity intrusion into the Delta (Kimmerer et al 2019). Extended low flow conditions led to salinity intrusion into the Delta, putting the state's water supply at risk.…”
Section: Barriersmentioning
confidence: 99%
“…Water managers took the remarkable step of installing a temporary rock barrier during 2015 in False River, one of the key corridors through which salinity enters the central Delta ("Drought Barrier"; Figure 1). Kimmerer et al (2019) concluded that the barrier successfully prevented landward intrusion of salt by reducing tidal dispersion in Franks Tract, a flooded island that affect Delta water quality and hydrodynamics.…”
Section: Barriersmentioning
confidence: 99%
“…The extreme 2012-2016 drought again brought attention to salinity barriers, although the required studies, permitting, and vetting were not in place until 2015 (AECOM 2015). However, several thoughtful studies were implemented to examine barrier effects on changes in the salinity field, water quality, food web dynamics, and invasive clam distribution (2015 presentation by E. Ateljevich, unreferenced, see "Notes";CDWR 2017;Kimmerer et al 2019). These studies provide reasonably good evidence for the effectiveness of the drought barrier, and provide a model of rapid implementation of hypothesis-driven drought science.…”
Section: Scientific Studies Of the Droughtmentioning
confidence: 99%
“…Salinity Barriers. The temporary salinity barrier at False River was effectively implemented with supporting analysis and hypothesis-based monitoring, and was perhaps the best example of pairing management action and scientific study during the 2012-2016 drought (CDWR 2017;Kimmerer et al 2019). The barrier helped stabilize water quality in the southern Delta and was combined with scientific inquiries.…”
Section: Scientific Preparationmentioning
confidence: 99%